Immunohistochemical localization of adenylyl cyclase in rat brain indicates a highly selective concentration at synapses. - Mons, N (1995)
Only three isoforms of adenylyl cyclase (EC 4.6.1.1) mRNAs (AC1, -2, and -5) are expressed at high levels in rat brain. AC1 occurs predominantly in hippocampus and cerebellum, AC5 is restricted to the basal ganglia, whereas AC2 is more widely expressed, but at much lower levels. The distribution and abundance of adenylyl cyclase protein were examined by immunohistochemistry with an antiserum that recognizes a peptide sequence shared by all known mammalian adenylyl cyclase isoforms. The immunoreactivity in striatum and hippocampus could be readily interpreted within the context of previous in situ hybridization studies. However, extending the information that could be gathered by comparisons with in situ hybridization analysis, it was apparent that staining was confined to the neuropil--corresponding to immunoreactive dendrites and axon terminals. Electron microscopy indicated a remarkably selective subcellular distribution of adenylyl cyclase protein. In the CA1 area of the hippocampus, the densest immunoreactivity was seen in postsynaptic densities in dendritic spine heads. Labeled presynaptic axon terminals were also observed, indicating the participation of adenylyl cyclase in the regulation of neurotransmitter release. The selective concentration of adenylyl cyclases at synaptic sites provides morphological data for understanding the pre- and postsynaptic roles of adenylyl cyclase in discrete neuronal circuits in rat brain. The apparent clustering of adenylyl cyclases, coupled with other data that suggest higher-order associations of regulatory elements including G proteins, N-methyl-D-aspartate receptors, and cAMP-dependent protein kinases, suggests not only that the primary structural information has been encoded to render the cAMP system responsive to the Ca(2+)-signaling system but also that higher-order strictures are in place to ensure that Ca2+ signals are economically delivered and propagated.